Comprehension Instruction for Tier 2 Early Learners: A Scaffolded Apprenticeship for Close Reading of Informational Text. (February 2020) - Mariage, Troy V.; Englert, Carol Sue; Mariage, Mary F.
This exploratory case study used a mixed-methods pre-/post-intervention design to study the impact of an intervention on reading comprehension, annotation, and discussion quality. Five third-grade struggling readers who were part of a Tier 2 reading comprehension group were apprenticed into holding close-reading discussions of informational text. The teacher utilized an apprenticeship approach to provide explicit instruction and scaffolding to support four phases of close reading (discussion norms, main ideas, annotating text, discussion). Curriculum-based probes indicated that students improved their comprehension as measured by the total number of accurate main ideas recalled, the number of correct responses on quizzes, and the number and breadth of annotations. A standardized, norm-referenced measure of fluency (Reading Curriculum–Based Measurement [R-CBM]) and comprehension (MAZE) also showed improvements from fall to spring, with four of five participants changing levels from the winter to spring administration on the MAZE measure of comprehension. Discourse analysis revealed changes in discussion quality.